Answer :
Answer:
x = 2
Step-by-step explanation:
set the first equation equal to y
3y = 6 -x
multiply by 2
6y = 12 - 2x
plug into the second equation
6x - 6y = 4
6x - 12 + 2x = 4
8x - 12 = 4
8x = 16
x = 2
Answer:
x=2, y = 4/3
Step-by-step explanation:
substitute the value of x into the second equation
move 3y onto the right side.
x = 6-3y
now substitute the value of x into the second equation .
6(6-3y) +6y = 4. (solve for y now)
36 - 18y + 6y = 4
36 - 12y = 4
-12y = -32
y= 4/3
put back the value of y into either equation
x = 6 - 3(4/3)
x = 6 - 4
x = 2